Health Risk Behaviors of Male School-going Adolescents with Tribal Ethnicity from Jharkhand, India: The Global School-based Student Health Survey - Arif Ali; Fayaz Ahmad Paul; Shahid Eqbal (CHRISMED Journal of Health and Research)
Introduction: Risky behavior among adolescents is a major public health problem in India and it affects health both at that time and in later years. Poor mental health is strongly related to other health and development concerns in young people notably lower educational achievements, substance abuse, and violence. The aim of this study is to assess the health risk behaviors of male school-going tribal adolescents from Jharkhand, India. Methodology: The present study is a cross-sectional descriptive study design. Schools were selected from rural areas of Ranchi district, Jharkhand. Sociodemographic data sheet and the Global School-based Student Health Survey were administered. Results: A total of 780 male students participated in the study. In the present study, 3.46% of the respondents have felt lonely always during the past 12 months, and 1.15% of the students have seriously considered attempting suicide. In this survey, the prevalence of current alcohol use among students (i.e., drinking at least one drink containing alcohol on one or more of the past 30 days) was 14.35%. In the school survey, it was found that during the past 30 days, 1.41% of the students have used marijuana (cannabis) 20 or more times. During the past 30 days, 18.46% of the students reported that they smoked cigarettes all 30 days. Conclusion: The finding of the study shows that mental health scenarios and high-risk behaviors are prevalent among adolescents from the tribal community; considering their social, religious, cultural, and economic backgrounds, adequate psychosocial intervention plans can be made for early identification and adequate intervention. This information might help policymakers, health professionals, and researchers to incorporate prevention and treatment strategies to reduce risk behaviors and prevent psychiatric disorders among these adolescents.